Studies toward the development of implementation plan of coordinated cadastral system for Peninsular Malaysia - A. Kadir, Abd. Majid; Ses, Sahrum; Desa, Ghazali; Omar, Kamaludin; Omar, Abdullah Hisam (2002)
The objectives are: i. To develop and realize a geocentric based Cadastral Control Infrastructure (CCI) ii. To establish methodology for the Development of National Digital Cadastral Data Base iii. To develop techniques for integrating the digital Cadastral Data with Mapping Data iv. To address the Institutional Issues on the Implementation of CCS.